Growers' perceptions towards the needs of their downstream customers in the Western Australian apple supply chain - Mohd Nawi, Nolila; Batt, Peter J. (Universiti Putra Malaysia Press, 2015)
To succeed in an agribusiness, growers must understand what is required by their downstream customers. This paper explores the perceptions of apple growers in Western Australia towards the needs of their downstream customers. The results indicate that the most important factors that are perceived by growers to influence their downstream customer's choice of supplier are quality, price and continuity of supply. On the other hand, for downstream buyers, quality, price and a favourable long-term relationship were the most important factors that they used in selecting their preferred supplier. The growers' perception of their downstream customer's needs, and indeed, the criteria by which customers evaluate their alternative suppliers, are closely aligned. Both growers and downstream intermediaries identified quality and price as the major factors in selecting their preferred trading partners.